A Multifrequency Radar System for Detecting Humans and Characterizing Human Activities for Short-Range Through-Wall and Long-Range Foliage Penetration Applications. (16th April 2014) - Narayanan, Ram M.; Smith, Sonny; Gallagher, Kyle A.
Abstract : A multifrequency radar system for detecting humans and classifying their activities at short and long ranges is described. The short-range radar system operates within the S-Band frequency range for through-wall applications at distances of up to 3 m. It utilizes two separate waveforms which are selected via switching: a wide-band noise waveform or a continuous single tone. The long-range radar system operating in the W-Band millimeter-wave frequency range performs at distances of up to about 100 m in free space and up to about 30 m through light foliage. It employs a composite multimodal signal consisting of two waveforms, a wide-band noise waveform and an embedded single tone, which are summed and transmitted simultaneously. Matched filtering of the received and transmitted noise signals is performed to detect targets with high-range resolution, whereas the received single tone signal is used for the Doppler analysis. Doppler measurements are used to distinguish between different human movements and gestures using the characteristic micro-Doppler signals. Our measurements establish the ability of this system to detect and range humans and distinguish between different human movements at different ranges.